2018
DOI: 10.1126/sciadv.aau8131
|View full text |Cite
|
Sign up to set email alerts
|

Solid electrolyte interphases for high-energy aqueous aluminum electrochemical cells

Abstract: An artificial solid electrolyte interphase on aluminum enables aqueous batteries with high specific energy and good reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
274
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(283 citation statements)
references
References 37 publications
8
274
1
Order By: Relevance
“…Nonmetallic cations, e.g., proton (H + ), hydronium (H 3 O + ), and ammonium (NH 4 + ) ions, have rarely been regarded as charge carriers in aqueous battery chemistry for research and commercial applications, [ 1–3 ] where the mainstream attention located at the metal cations, such as Li + , Na + , Zn 2+ , and Al 3+ ions. [ 4–8 ] Most recently, Ji and co‐workers have pioneeringly reported several typical aqueous batteries utilizing H + and NH 4 + as charging carriers with outstanding electrochemical performance, especially for the ultrafast kinetics with high power density. [ 1,9 ] It could be ascribed to (1) nondiffusion‐controlled topochemistry between nonmetallic charging carriers and electrode framework during insertion/extraction process, resulting in pseudocapacitive‐dominated behavior; [ 1,9 ] (2) the lower molar mass and smaller hydrated ionic size of such non‐metallic charging carriers, which could result in fast diffusion in aqueous electrolytes.…”
Section: Figurementioning
confidence: 99%
“…Nonmetallic cations, e.g., proton (H + ), hydronium (H 3 O + ), and ammonium (NH 4 + ) ions, have rarely been regarded as charge carriers in aqueous battery chemistry for research and commercial applications, [ 1–3 ] where the mainstream attention located at the metal cations, such as Li + , Na + , Zn 2+ , and Al 3+ ions. [ 4–8 ] Most recently, Ji and co‐workers have pioneeringly reported several typical aqueous batteries utilizing H + and NH 4 + as charging carriers with outstanding electrochemical performance, especially for the ultrafast kinetics with high power density. [ 1,9 ] It could be ascribed to (1) nondiffusion‐controlled topochemistry between nonmetallic charging carriers and electrode framework during insertion/extraction process, resulting in pseudocapacitive‐dominated behavior; [ 1,9 ] (2) the lower molar mass and smaller hydrated ionic size of such non‐metallic charging carriers, which could result in fast diffusion in aqueous electrolytes.…”
Section: Figurementioning
confidence: 99%
“…Recently Zhao et al. reported an aluminum anode modified with ionic liquid and MnO 2 as a cathode for an AAIB . To date, only TiO 2 , V 2 O 5 , CuHCF, and spinel MnO 2 have been studied as electrode materials for AAIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a full cell was reported using a TiO 2 anode and a copper hexacyanoferrate cathode with Al 2 (SO 4 ) 3 as the electrolyte . Recently Zhao et al reported surface modified aluminum as an anode with a MnO 2 cathode in an aqueous AlCl 3 electrolyte . To date only TiO 2 , V 2 O 5 , CuHCF, Spinel MnO 2, Cryptomelane and MoO 3 have been studied as electrode materials for AAIBs.…”
Section: Introductionmentioning
confidence: 99%